2003
DOI: 10.1155/s0161171203201046
|View full text |Cite
|
Sign up to set email alerts
|

Total characters and Chebyshev polynomials

Abstract: The total character τ of a finite group G is defined as the sum of all the irreducible characters of G. K. W. Johnson asks when it is possible to express τ as a polynomial with integer coefficients in a single irreducible character. In this paper, we give a complete answer to Johnson's question for all finite dihedral groups. In particular, we show that, when such a polynomial exists, it is unique and it is the sum of certain Chebyshev polynomials of the first kind in any faithful irreducible character o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We call such a polynomial f (x) ∈ Q[x], if it exists, a generalized Johnson polynomial of G. (When we insist that the coefficients are integral, we will say that f (x) is an integral Johnson polynomial.) This problem has been studied for dihedral groups D 2n in [16], where it is proved that D 2n has a generalized Johnson polynomial if and only if 8 n. In [17] and [18], the second author along with R. Sarma and B. Sury, investigated the existence of generalized Johnson polynomials on several classes of p-groups. In all of those cases, they showed that such groups can only have a generalized Johnson polynomial when the group has nilpotence class 2 and a cyclic center.…”
Section: Theorem 11 Let G Be a Nilpotent Group Of Nilpotence Class 2mentioning
confidence: 99%
See 1 more Smart Citation
“…We call such a polynomial f (x) ∈ Q[x], if it exists, a generalized Johnson polynomial of G. (When we insist that the coefficients are integral, we will say that f (x) is an integral Johnson polynomial.) This problem has been studied for dihedral groups D 2n in [16], where it is proved that D 2n has a generalized Johnson polynomial if and only if 8 n. In [17] and [18], the second author along with R. Sarma and B. Sury, investigated the existence of generalized Johnson polynomials on several classes of p-groups. In all of those cases, they showed that such groups can only have a generalized Johnson polynomial when the group has nilpotence class 2 and a cyclic center.…”
Section: Theorem 11 Let G Be a Nilpotent Group Of Nilpotence Class 2mentioning
confidence: 99%
“…Motivated by this, K. W. Johnson raised the following question: does there exist an irreducible character χ of G and a monic polynomial f (x) ∈ Z[x] such that f (χ) = τ G ? (See [16].) If for the group G, there is a monic polynomial f (x) ∈ Z[x] such that f (χ) = τ G , then we say G has a Johnson polynomial.…”
mentioning
confidence: 99%